Cournot competition in wholesale electricity markets: The Nordic power exchange, Nord Pool - Erik Lundin; Thomas P. Tangerås (Research Institute of Industrial Economics (IFN), 2017)
Horizontal shifts in bid curves observed in wholesale electricity markets are consistent with Cournot competition. Quantity competition reduces the informational requirements associated with evaluating market performance because the markups of all producers then depend on the same inverse residual demand curve instead of one for each firm. We apply the model to the day-ahead market of the Nordic power exchange, Nord Pool, for the years 2011-2013. Results suggest that mark-ups were 8-11 percent. We find some support for the hypothesis that the division of Sweden into price areas in 2011 increased the exercise of market power.
Keywords: D22; D43; D44; D4; 330; Cournot competition; Market design; Market performance; Nord Pool; Walrasian auction; Wholesale electricity market